Complement factor H polymorphism rs1061170 and the effect of cigarette smoking on the risk of lung cancer - Ezzeldin, Nada; El-Lebedy, Dalia; Darwish, Amira; El-Bastawissy, Ahmed; Shalaby, Alaa Eldin (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: Complement factor H (CFH) has been known to inhibit the complement pathway and to contribute to tumour growth by suppressing the anti-tumour cell mediated response in cell lines from several malignancies. We examined the association of Try402His single nucleotide polymorphism in CFH gene with lung cancer and the interaction with cigarette smoking. Material and methods: This case-control study included 80 primary lung cancer patients and 106 control subjects who were genotyped for Try402His (rs1061170) by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. Results : Variant genotypes (Tyr/His and His/His) were overpresented among patients compared to controls (p = 0.03, OR = 2.510, 95% CI: 1.068–5.899), and the frequency of variant H allele was significantly overexpressed in cases compared to controls (p = 0.021). Tyr/His genotype was identified in 100% of small cell lung cancer (SCLC) patients vs. 34.5% of non-SCLC (NSCLC), while 20.7% of NSCLC patients were homozygous for the variant allele (His/His) (p = 0.001). Binary logistic regression analysis revealed a 2.5 times greater estimated risk for NSCLC than for SCLC among variant allele carriers, and a 7.3-fold increased risk of lung cancer among variant allele smoking carriers vs. 1.3-fold increased risk among wild allele smoking carriers. Moreover, the stage of cancer positively correlated with smoking and pack-years in allele H carriers, and the correlation was stronger among those who were homozygous for it (His/His) than those who were heterozygous (Tyr/His). Conclusions: CFH 402H variant is a smoking-related risk factor for lung cancer, particularly the NSCLC.